Can targeted poverty alleviation reduce criminal offenses? Empirical evidence from China judgments online data - Mengjie Yi; Jiasheng Li; Guangjun Shen (China Economic Quarterly International, 2024)
Targeted Poverty Alleviation (TPA) is an important leverage for China to overcome poverty. While its economic effects are well studied, less is known about the social impact of TPA. Based on trial documents data from the China Judgments Online, we use DID method and find the growth rate of criminal offenses reduced by over 20% after the implementation of TPA. The income growth effect from TPA is the primary mechanism for suppressing criminal crimes. Improved employment plays a role as well. Our work not only reveals the relationship between TPA and the enhancement of societal security, characterized by fewer criminal offenses, in the background of completing the first Centenary Goal, but also sheds light on how to fulfil the Peaceful China Initiative in the second Centenary Goal.